Limites constitucionais ao poder legislativo na tipificação de infrações administrativas de polícia e na determinação do regime jurídico de suas sanções - Sirlene Nunes Aredes (2013)
The aim of the current work is to question the theory of autonomy and independency within Judicial levels in the applied law in Brazil. This study demonstrates the applicability of constitutional principles related to state punishment to Administrative Law Sanctioning. It also defends the applicability of the principle of ne bis in idem (double jeopardy) in the Brazilian legal system within the relationship between punitive levels. This study is a theoretical research on the constitutional norms that limit the punitive power exerted by the Public Administration and the contrast of these norms and the doctrinal and jurisprudential treatments which are relevant to the topic. We used primary and secondary direct sources. To achieve our results, we used as theoretical frameworks the theory of the unity of States punitive power and the agnostic theory of punishment. With a critical-methodological attitude and from a juridical-dogmatic viewpoint, this study has incorporated interdisciplinary knowledge. Moreover, it has used interpretive legal research and propositional legal research, the hypothetical-deductive reasoning and the procedure of theoretical analysis. The research has concluded that the theory of autonomy and independence of the criminal and administrative law, as determined by constitutional legislation and supported by the Brazilian doctrine and jurisprudence, is not consistent with the protection of fundamental rights determined by CRFB/88 (Brazilian constitution of 1988). Furthermore, the state punishment represents a broad concept that covers the criminal law, non-criminal law and the administrative law while that there is no substantive, quantitative or formal criteria, constitutionally imposed, which guarantees the independence between criminal and administrative spheres of law. Besides, when the Public Administration, applies administrative sanctions, they carry out the same activity as the judiciary when the latter applies criminal sanctions or other punitive sanctions. It was found that the Legislative Power CRFB/88 ensures discretionary to determine the punitive approach to be used with most types of offence, but that the Legislative Power can use only one for each offence, given the applicability of ne bis in idem (double jeopardy) in the relationship between the approaches. It was also found that the discretionary of the Legislative Power is partially limited by CRFB/88. Likewise, the Legislative Power is bound by constitutional guarantees and imposed to the inherent punitive power of the rule of law, so that, regardless of the sphere in which this power manifests these principles must be respected. The inherent principles in the rule of law which cannot be changed by the Legislative Power are typicality, the legal coverage for typifying behavior and legal imposition of sanctions, subjective and personal responsibility, the presumption of innocence and the ne bis in idem (double jeopardy). It is argued that the ne bis in idem (double jeopardy) binds the Legislative Power and who applies the norm.